Moisture: A Stability Problem - Saini, Navdeep (International Journal of Pharmaceutical & Biological Archive, 2011)
Presence of moisture influences chemical stability, crystal structure, powder flow, compaction lubricity, dissolution rate, and polymer film permeability in solid dosage forms and lead to growth of microorganisms, change in thixotropy in semi-solid dosage forms. Moreover, unit operations obviously depending on the amount and state of water present are also influenced by it. Therefore, moisture influences the properties of individual active ingredients and excipients, and it is essential to characterize the effect of moisture on these individual components. This article lay emphasis on determination of moisture by various methods and illustrates the changes induced by moisture on several product and process attributes.